Improving social participation of adolescents with a visual impairment with community-based mentoring: results from a randomized controlled trial. Issue 22 (22nd October 2020) - Heppe, Eline C. M.; Willemen, Agnes M.; Kef, Sabina; Schuengel, Carlo
Abstract: Purpose: The efficacy of a community-based mentoring program for adolescents with a visual impairment vs. care-as-usual was tested on social participation including satisfaction with social support. Materials and methods: Adolescents (15–22 years; 46% boys) were randomized to an intervention group with mentors with visual impairment ( N  = 25), an intervention group with mentors without visual impairment ( N  = 26), or care-as-usual ( N  = 25). One-on-one mentoring activities regarded school/work, leisure activities, and social relationships. Results and conclusions: Multilevel growth modelling revealed no effect of mentoring on changes in social participation compared to the care-as-usual group (participation [95% CI –0.30, 0.21, d  = 0.1]; social participation composite [95% CI –0.24, 0.26, d  = 0.24]). Mentees matched to mentors with visual impairments increased more on satisfaction with their social support compared to mentees matched to mentors without impairments and the care-as-usual group [95% CI 0.02, 0.49, d  = 0.38]. Age, characteristics of the impairment, and number of match meetings were not associated with change in social participation during the mentoring program. This evaluation showed no benefit of mentoring for social participation of adolescents with a visual impairment. The value of mentors and mentees sharing the same disability needs further investigation. This trial is registered in the Netherlands Trial Register NTR4768. Implications for rehabilitation: A community-based mentoring program resulted in no benefits for adolescents with a visual impairment on their social participation. A community-based mentoring program should not replace care-as-usual provided to young people with a visual impairment in the Netherlands. It could only be thought of as an additional service within rehabilitation. Matching mentees and mentors based on sharing the same disability could strengthen the effect of a community-based mentoring program. However, these benefits are rather small. Providing additional support for the social participation of young people with a visual impairment might be especially helpful for those with a progressive impairment and with comorbid problems.